Innovative Marketing: Strategies for Engaging the Hyper-Connected Consumer - Abdurrahman Sadikin; M Ali Musri. S; Rini Puji Astuti (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study investigates the impact of innovative marketing strategies on consumer engagement, focusing on both direct and indirect effects through digital consumer behavior and technology adoption. Using a sample of 200 Shopee platform users, data were collected via an online survey and analyzed using SmartPLS. The results reveal that innovative marketing strategies have a significant positive effect on consumer engagement, both directly and indirectly. Specifically, these strategies enhance digital consumer behavior and facilitate technology adoption, which in turn contribute to increased consumer engagement. The path analysis demonstrates that while direct effects are substantial, the indirect pathways through digital behavior and technology use further amplify consumer engagement. These findings highlight the critical role of innovative marketing in shaping consumer interactions and optimizing engagement in the digital era, offering practical insights for brands aiming to leverage advanced marketing techniques and technology to deepen consumer involvement.